The Treatment of Functional Dyspepsia Based on "Brain-gut Co-regulation" Theory - Yue, Yuting; Wang, Min; Tang, Zhifeng (Journal of Contemporary Medical Practice, 2024)
Functional dyspepsia is a typical functional gastrointestinal disease with a high incidence and a long course of disease that is difficult to cure, its pathogenesis can be summarized as "imbalance of the central center of the gods" and "blockage of the stomach and intestines". Now we take the idea of "Brain-Gut Coordinating" as an overall guide, and specifically use methods such as invigorating spleen and soothing liver and regulating the mind, pungent open and bitter down bearing and regulating center. In order to improve the patient's digestive symptoms and relieve the patient's mental and psychological discomfort, so as to achieve better clinical efficacy, and providing new ideas for the treatment of functional dyspepsia.